Multi-Omics Analysis of Molecular Characteristics and Carcinogenic Effect of NFE2L3 in Pan-Cancer - Liu, Mengxiao; Wei, Hui; Yang, Jing; Chen, Xia; Wang, Haoying; Zheng, Ya; Wang, Yuping; Zhou, Yongning (Frontiers in Genetics, 2022)
Nuclear factor erythroid 2-like 3 (NFE2L3), as known as NRF3, is a nuclear transcription factor and is associated with the pathogenesis and progression of human tumors. In order to more systematically and comprehensively explore the role of NFE2L3 in the tumor, we performed a pan-cancer analysis through multi-omics data, including gene expression analysis, diagnostic and prognostic analysis, epigenetic methylation analysis, gene alteration analysis, immune feature analysis, functional enrichment analysis, and tumor cell functional status analysis. Notably, we further explored the molecular mechanism of NFE2L3 in liver hepatocellular carcinoma (LIHC). We analyzed the relationship between NFE2L3 expression and survival prognosis of patients with LIHC and constructed a nomogram prediction model. Our study showed that the expression level of NFE2L3 is generally up-regulated in most cancers, and this suggested that NFE2L3 may play an important role in promoting cancer progression. NFE2L3 showed a certain potential in cancer diagnosis and prognostic value. NFE2L3 expression was closely related to DNA methylation, genetic alteration, immune signature, and tumor cell functional status in pan-cancer. Furthermore, we demonstrated that NFE2L3 was an independent risk factor for LIHC and the nomogram model based on NFE2L3 expression had a good prediction efficiency for the overall survival of patients with LIHC. In summary, our study indicated that NFE2L3 may be an important molecular biomarker for the diagnosis and prognosis of pan-cancer. NFE2L3 is expected to become a potential molecular target for the treatment of tumors.